2004
DOI: 10.1161/01.atv.0000099881.83261.d4
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and Association Between Distinct Variants of the APOA1/C3/A4/A5 Gene Cluster and Familial Combined Hyperlipidemia

Abstract: Objective-Combined hyperlipidemia is a common disorder, characterized by a highly atherogenic lipoprotein profile and a substantially increased risk of coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
72
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 52 publications
7
72
1
1
Order By: Relevance
“…However, because there were high correlations between the phenotypes and marker alleles were interdependent, there was no necessity to adjust for multiple comparisons. 5,29,30 In addition, type I errors are random and patterns in results that confirm previous reports should be given more weight than isolated results with a single low P-value. 5,29 Moreover, correction for multiple comparisons largely increases the likelihood of type II errors and important differences are considered nonsignificant.…”
Section: Discussionmentioning
confidence: 51%
“…However, because there were high correlations between the phenotypes and marker alleles were interdependent, there was no necessity to adjust for multiple comparisons. 5,29,30 In addition, type I errors are random and patterns in results that confirm previous reports should be given more weight than isolated results with a single low P-value. 5,29 Moreover, correction for multiple comparisons largely increases the likelihood of type II errors and important differences are considered nonsignificant.…”
Section: Discussionmentioning
confidence: 51%
“…Two common haplotypes were defined: APOA5*2 based on −1131C→T and APOA5*3 based on the c56C→G polymorphism [8]. Association studies have shown a positive correlation between plasma triglycerides and the rare variant of the c56C→G, as well as the rare variant of the −1131T→C in a number of different populations, patient cohorts, and ethnic groups [7,12,13,[25][26][27][28][29][30][31][32]. In the present study, the associations between these genetic variations and plasma triglycerides did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 72%
“…Our findings, however, suggest that apoAV is not involved in the pathogenesis of the secondary hypertriglyceridaemia associated with obesity and insulin resistance in these rats. In humans with hypertriglyceridaemia or familial combined hyperlipidaemia, polymorphisms in APOA5 show a strong association with plasma triglyceride levels across several ethnic groups [2][3][4]39]. ApoAV deficiency leads to severe hypertriglyceridaemia [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The gene for apoAV (APOA5) is part of the APOA1/A4/C3/A5 gene cluster on chromosome 11 in man, and APOA5 is predominantly expressed in the liver. Human APOA5 polymorphisms are associated with elevated plasma triglyceride levels [2][3][4]. Studies in genetically modified mice and adenovirus overexpression experiments revealed a strong triglyceride-lowering effect of apoAV [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%